School Management in Enhancing Human Resource Performance: A Multi-Case Study at State Islamic Senior High School 1 Trenggalek and State Senior High School 1 Trenggalek - Toyib Mashuri; Ahmad Tanzeh; Asrop Safi’i (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2026)
The objective of this study is to formulate new propositions on school management based on the findings obtained from the two schools under investigation, namely: (1) school planning in improving teacher performance at State Islamic Senior High School 1 Trenggalek and State Senior High School 1 Trenggalek; (2) the implementation of school management in improving teacher performance at State Islamic Senior High School 1 Trenggalek and State Senior High School 1 Trenggalek; and (3) school supervision in improving teacher performance at State Islamic Senior High School 1 Trenggalek and State Senior High School 1 Trenggalek. This research employed a case study approach with a qualitative research design. The researcher’s presence in the schools served as the primary instrument, supported by non-human instruments as complementary tools. Data sources consisted of primary data in the form of words and actions observed from principals, vice principals, teachers, and administrative staff, as well as secondary data in the form of school documents. Data collection techniques included in-depth interviews, participant observation, and documentation. Data analysis was conducted using the Miles, Huberman, and Saldaña model, which comprises data condensation, data display, and conclusion drawing. The data analysis techniques applied were (1) single-case analysis conducted separately in each school and (2) cross-case analysis conducted by comparing and synthesizing data across cases. The research findings indicate that: (1) school planning to improve teacher performance carried out by principals included (a) adherence to the school’s vision, mission, and objectives; (b) consideration of the results of the School Self-Evaluation (EDS) through SWOT analysis to enhance teacher performance; and (c) the formulation of school activity plans collaboratively with the school committee; (2) the implementation of school management to improve teacher performance by principals involved (a) mobilizing and motivating all members of the school community and utilizing all available school resources; (b) controlling and supervising the implementation of school activities; (c) securing support for school activities from parents/guardians, the school committee, and the community; (d) fulfilling teachers’ needs; (e) proportional distribution of tasks and clear job descriptions aligned with teachers’ competencies; (f) enhancement of teacher competencies; and (g) fostering a culture of mutual cooperation, care, and respect among school members to improve teacher performance.